Teachers' Directive Speech Acts in News Text Learning for Class VII of SMP Negeri 16 Kerinci, Indonesia - Almira, Fidela; Tressyalina (Manunggal Halim Jaya, 2025)
The purpose of this study is to describe the form of speech behavior of Indonesian teachers in learning news texts in grade VII of SMP Negeri 16 Kerinci. In this study, a qualitative approach with a descriptive method is used. The data used was the speech of an Indonesian teacher at SMP Negeri 16 Kerinci. The data source is Mrs. Liska Anggela, S.Pd. Data collection techniques use SLBC and Record techniques. The results of this study obtained five forms of directive speech used by teachers: telling, begging, suggesting, demanding, and challenging. Of the five forms of speech, the most dominant speech is the act of commanding. During the learning process, teachers tend to use directive speech actions. The form of directive speech used is marked with the words